Traditional midwifery in Chocó, Colombia. A case study of their recognition and integration in the Colombian health system by local and national actors, and international cooperation between 2017 and 2025 - Yapp,Gabrielle Claire; Bejarano,Lorena (2026)
Although maternal mortality rates have decreased globally, they remain a development concern, with their preventability and uneven burden highlighting inequalities both between and within countries. This study, through Post-Development Theory, the Epistemologies of the South framework, and Social Reproduction Theory, examines the integration and recognition of traditional-midwives in the Chocó region of Colombia within the health system from a multilevel approach. Using a qualitative methodology, this study develops a documentary review and conducts semi-structured interviews with key stakeholders. The macro-level results reveal that national and departmental policies and legal frameworks have produced symbolic recognition without ensuring real integration. At the meso level, institutional and international good intentions and efforts towards collaborative healthcare approaches coexist with academic disconnection and the absence of dignified labour conditions. At the micro level, the experiences and contributions of traditional-midwives expose a gap between community level recognition and support, and institutional ambivalence, contextualised in challenging working conditions. In conclusion, the recognition and integration of traditional-midwives is a complex process marked by structural inequalities and institutional racism. While there are efforts toward hybrid practices, many of these fall on traditional-midwives, rather than on a health system willing to change its structure to incorporate them genuinely.
Keywords: Traditional Midwifery; Chocó; Colombia; Integration; Recognition